Microprocessors the off-beat generation. - Geppert, L.
Three innovative processors across the full range of performance are targeted toward applications in powerful supercomputing, multimedia broadband communications and programmable logic
Keywords: Microprocessors; Multimedia broadband communications; Off-beat generation; Performance; Programmable logic; Supercomputing